Effect of Ground Plane Deformation on Electrical Performance of Air Microstrip Antennas - Wei Wang; Yanjun Wang; Shunxi Lou; Shuo Zhang; Yatian Zhou (International Journal of Antennas and Propagation)
This paper covers the variation of electrical performance of air microstrip antennas due to its ground plane deformation. A typical sinusoidal function is utilized to characterize the shape of deformation, based on which different shapes of ground plane can be obtained by changing control parameters. From the simulation results by HFSS, there is a strong linear relationship between the offset of resonant frequency and the amplitude of deformation. The equivalent thickness of the air medium is introduced into the calculation model, and then the mathematical model is established to describe the resonant frequency offset and deformation amplitude. It can also be seen from the radiation pattern that the directivity decreases with the increase of deformation. The proposed method can be used to predict the effect of ground plane deformation on electrical performance of air microstrip antennas.